2012
DOI: 10.1021/jp304521k
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Vanadium Pentoxide Deposited by ALD

Abstract: The experimental work is carried out at the NAFUMA (Nano-and Functional Materials) group under the supervision of Prof.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 172 publications
(267 reference statements)
2
25
0
Order By: Relevance
“…Heat treated films display very different optical properties with increased transmittance, except at room temperature and λ > 1600 nm, and no trace of thermochromism. These data are consistent with those expected for V 2 O 5 [25][26][27][28][29][30][31], and it is obvious that the vanadium-based film is fully oxidized. Data were recorded also for τ h = 80 °C and RH = 80%, but otherwise as before.…”
Section: Equipment and Procedures For Ageing Testssupporting
confidence: 90%
“…Heat treated films display very different optical properties with increased transmittance, except at room temperature and λ > 1600 nm, and no trace of thermochromism. These data are consistent with those expected for V 2 O 5 [25][26][27][28][29][30][31], and it is obvious that the vanadium-based film is fully oxidized. Data were recorded also for τ h = 80 °C and RH = 80%, but otherwise as before.…”
Section: Equipment and Procedures For Ageing Testssupporting
confidence: 90%
“…Dagur et al reported the direct growth of the monoclinic VO 2 at 475°C starting from VO(acac) 2 and molecular oxygen . The ALD growth of V 2 O 5 above 196°C, starting from VO(thd) 2 (thd: tetramethyl heptanedionate) and ozone as reactants, was reported, while amorphous films were obtained at lower temperatures …”
Section: Atomic Layer Growth Modementioning
confidence: 99%
“…[190] The ALD growth of V 2 O 5 above 196°C, starting from VO(thd) 2 (thd: tetramethyl heptanedionate) and ozone as reactants, was reported, while amorphous films were obtained at lower temperatures. [189] The reaction of VOCl 3 with water vapor was implemented at 490°C for the ALD of vanadium oxide. [191] This process led to the formation of a mixture of several crystalline vanadium oxide compounds.…”
Section: Atomic Layer Growth Modementioning
confidence: 99%
“…4,20,21 With the ALD process, VO x thin lms have been grown using different metal, metal-organic, and metal-halide precursors as the source material for vanadium and H 2 O, H 2 O 2 , O 3 , molecular O 2 , and O 2 plasma as the oxidizing reactant. 4,14,17,[22][23][24] Among these, vanadyl triisopropoxide (VTIP; V 5+ ) is the most popular vanadium precursor used for the ALD growth process. 4 Conventional ALDgrown VO x thin lms are amorphous in nature, 25,26 except for limited cases where crystalline lms were successfully obtained.…”
Section: Introductionmentioning
confidence: 99%